Sex-Differences in Language and Socio-emotional Skills in Early Childhood - Rosangela Bando Grana; Florencia López-Bóo; Xia Li (Inter-American Development Bank (IDB), 2016)
This study explores sex differences in language and socio-emotional skills. It focuses on children 7 months old to 6 years old in Chile in 2012 and Nicaragua in 2013. A focus on young children allowed for ruling out a set of environmental and identity effects to explain the gap. Females had an advantage in both countries and both dimensions. Males in Chile scored at -0.13 standard deviations (SD) in language in the distribution of females. In addition, males scored at -0.20 SD in socio-emotional skills. The gaps in Nicaragua were not statistically different to those in Chile. Thus geographical and cultural variation across the two countries did not affect the gap. Within countries, variation in family characteristics, parenting practices and health investments did not explain the gap either. These findings shed light on the role of biological and environmental factors to explain sex gaps. The identification of the role of these factors is necessary to inform policy.
hdl:11319/7808
Keywords: I25; J13; J16; O15; Z13; 330; gender gaps; sex gaps; language; social skills; emotional skills; early childhood